A life cycle risk assessment of nanopesticides in freshwater - Mingyan Ke; Keshuo Zhang; Andrea L. Hicks; Fan Wu; Jing You (Environmental Science and Ecotechnology)
Conventional ecological risk assessments prioritize downstream anthropogenic impacts, overlooking risks arising from upstream processes involving highly hazardous substances and indirect emissions. This narrow focus obscures high-risk hotspots and renders traditional methodologies ill-suited for evaluating novel chemical entities. Nanopesticides, designed for targeted delivery of pesticidal active ingredients, are increasingly deployed to enhance efficiency, yet their altered environmental fate and transport dynamics may reshape end-of-life risks while their full lifecycle impacts remain uncharacterized. Here, we address this gap using imidacloprid (IMI) and its nano-encapsulated variant (nano-IMI) as case studies. By applying life cycle assessment and integrating the USEtox ecotoxicity model with the nano-specific SimpleBox4Nano framework, we quantify ''cradle-to-gate'' environmental impacts and derive substance-specific ecotoxicity metrics, enabling systematic characterization of end-of-life risks associated with these formulations. Production-stage ecological risks of nano-IMI (4.63 × 103 CTUe) are approximately four times greater than those for conventional IMI (1.18 × 103 CTUe). However, end-of-life freshwater ecological risks from nano-IMI emissions (0.012–6.93 × 104 CTUe) are 2–5 orders of magnitude lower compared with IMI (1.59 × 103–6.13 × 106 CTUe), accounting for rainfall variability, toxicity data selection, fate, and environmental transport scenarios. Under equivalent rainfall conditions, nano-IMI exhibited up to three orders of magnitude lower integrated life-cycle freshwater ecological risks, underscoring its potential as an environmentally preferable alternative to conventional IMI. This research introduces a comprehensive and novel methodology for evaluating engineered nanomaterial alternatives across realistic environmental scenarios, providing essential insights into nanopesticide risk assessment throughout their lifecycle.